The Influence of Unemployment Rate and Labor Structure on Economic Growth in West Java for the Period 2019-2024 - Rohadin; Muhafidin, Didin; Setiadi, Ade; Nurcahyo, Arif (GoAcademica Research & Publishing, 2025)
This study aims to analyze the effect of unemployment rate and workforce structure on economic growth in West Java during the period 2019-2024. The method used is path analysis with secondary data obtained from various official sources. The results of the analysis show that the relationship between unemployment rate (X1) and workforce structure (X2) on economic growth (Y) tends to be weak, with an R-squared value of 2.8%, indicating that the model is only able to explain 2.8% of the variation in economic growth. This study concludes that unemployment rate and workforce structure do not have a significant effect on economic growth in West Java during the study period. Other factors not included in the model are likely to contribute more to economic growth. This finding underscores the importance of considering additional variables and improving research methods in regional economic analysis.